Community Empowerment for Family Welfare Program Members in Hydroponic Vegetable Cultivation within Household Surroundings - Yudha Adi Kusuma; Halwa Annisa Khoiri; Deby Ika Hariani; Denton Bukhori; Tita Talitha; Saufik Lutfianto; Irna Tri Yuniahastuti (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
The scarcity of available land does not impede the development of productive activities. Hydroponic vegetable cultivation emerges as a viable solution for maximizing the utilization of limited land. Hydroponic vegetables have been shown to possess enhanced nutritional value and to be free from pesticides. The cultivation of hydroponic vegetables has the potential to augment family income. The objective of this Community Service Program (CSP) is to empower Family Welfare Empowerment (FWE) members in Babadan Village through counseling and mentoring. The hydroponic vegetable cultivation media utilizes readily available household items. The CSP is a multifaceted program that includes a location survey, planning, counseling, mentoring, and evaluation. The results of the CSP showed that 80% of the participants understood the hydroponic vegetable growing system. After the activity was completed, CSP participants practiced hydroponic vegetable cultivation independently. The principle of Reduce, Reuse, Recycle (3R) is applied as an operational saving step. This CSP activity improves participants' skills and supports economic independence and awareness of the importance of healthy food. The future expansion of this CSP initiative entails the diversification of hydroponic plant species, the establishment of a hydroponic community, and enhanced access to marketing opportunities for produce. The integration of local markets and digital platforms is anticipated to be optimized.